'Fortified' wines volatile composition: Effect of different postharvest dehydration conditions of wine grapes cv. Malvasia moscata (Vitis vinifera L.). (15th March 2017) - Urcan, Delia Elena; Giacosa, Simone; Torchio, Fabrizio; Río Segade, Susana; Raimondi, Stefano; Bertolino, Marta; Gerbi, Vincenzo; Pop, Nastasia; Rolle, Luca
Highlights: The effect of dehydration rate was evaluated on Malvasia moscata aromatic cultivar. Fresh grape ripeness was related to dehydrated grape volatiles for the first time. The dehydration of the riper berries resulted in terpene-richer dehydrated grapes. Fast grape dehydration rate led to an increase in the content of free terpenes. Fortified wines made from fast dehydrated grapes were richer in volatile compounds. Abstract: The impact of postharvest dehydration on the volatile composition of Malvasia moscata grapes and fortified wines produced from them was assessed. The ripeness effect of fresh grapes on volatile compounds of dehydrated grapes was evaluated for the first time in this study. Fresh grape berries were densimetrically sorted, and more represented density classes were selected. Dehydration of riper berries (20.5 °Brix) led to volatile profiles richer in terpenes, particularly linalool and geraniol. The effect of dehydration rate on the volatile composition of dehydrated grapes and fortified wines was also evaluated. Fast dehydration grapes were richer in total free terpenes, and the resulting wines contained greater amounts of volatile compounds. The predominant compounds were free esters, but linalool, rose oxide, citronellol and geraniol can also contribute to wine aroma, particularly for fast dehydration. β-Damascenone can be an active odorant, although its contribution was greater in wines made from slow dehydrated grapes.